IMPLEMENTATION OF EFFECTIVE CUTTING STRATEGIES IN HIGH SPEED MACHINING FOR MID-RANGE CNC MACHINES - Vasquez Ospina, Angel Andres
This work addresses a comparative analysis through experimental observation between conventional machining strategies and high-speed machining strategies, specifically truncal machining. For this, SENA CDITI acquired hydraulic assembly devices for parts, tools and the project team designed a test part, which was machined in 1045 steel and 7075 duralumin material using the two machining strategies to be compared. During the process, variables such as energy consumption, machining time and metrological deviation were measured, to finally perform data analysis and present results with an assessment of the possible advantages and disadvantages of using truncal machining versus conventional machining.